The Effect of Corporate Governance and Executive Incentives on Tax Avoidance of Food and Beverage Sector Companies - Mardiana, Mardiana; Masrullah, Masrullah; Khadijah Darwin (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this study is to determine the effect of corporate governance and executive incentives on tax avoidance listed on the IDX. The population in this study is food and beverage sector manufacturing companies listed on the IDX for the 2019-2022 period. The samples in this study used purposive sampling sample techniques, based on the criteria set, 40 samples were obtained. The type of data used is secondary data in the form of the company's Annual Report. The data analysis methods used in this study are descriptive statistics, classical assumption tests, multiple linear regression analysis and hypothesis tests. Based on the results of data research using the Eviews 12 application shows that corporate governance has a t-count of -0.191 < 1.68709 t-table value and executive incentives have a t-count of -0.584 < 1.68709 t-table value, then the author draws a conclusion that corporate governance with institutional ownership, managerial ownership and independent commissioners has no effect on tax avoidance And executive incentives also have no effect on tax avoidance.